Laserstrahlregelung und Optikdiagnostik in der Strahlführung einer CO2-Hochleistungslaseranlage - Hutfless, Joachim (Friedrich-Alexander-Universität Erlangen-Nürnberg, 1993)
Within the framework of this research new sensor and control units were developed for the closed-loop control of the laser beam and the optical component quality. The sensor concepts aim at an application close to the process as well as an on-line capability. In particular, the laser beam is sampled at its rim with a thermo-couple sensor measuring the beam position and radius. These two beam parameters are controlled by dynamical optical elements. The optical diagnostic system is based on a geometrical-optical test principle and supplies a measure for the thermal load of the optic